A generalization of the dichromatic polynomial of a graph. (1981) - Farrell, E. J.
Abstract : The Subgraph polynomial fo a graph pair( G, H ), whereH ⫅ G, is defined. By assigning particular weights to the variables, it is shown that this polynomial reduces to the dichromatic polynomial ofG . This idea of a graph pair leads to a dual generalization of the dichromatic polynomial.